1985
DOI: 10.4039/ent1171565-12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adhesive on the Spectral Reflectance of Insect Traps

Abstract: Can. Enr. 117: 1559-1564 (1985) The effect of trap color on sticky-trap catches of Pholetesor ornigis Weed was studied in experimental and commercial apple orchards during each of the parasite's 3 yearly activity periods during 1982-1984. Seven enamel and 5 fluorescent paints were compared in 8 trials. There was considerable between-trial variation in the percentage of the total number of P. ornigis caught on a trap of one color. Trap color had a significant effect on the total number of parasites caught. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
1
5
0
Order By: Relevance
“…The influence of colour was less marked with vertical sticky traps than with horizontal water traps, in agreement with the findings of Heathcote (1957). No attempt has been made to relate the effect of sticky trap colour to the wavelength of light emitted since it is known that the adhesive used on sticky traps may considerably affect the spectral reflectance of the original colour (Brach & Trimble, 1985).…”
Section: Discussionsupporting
confidence: 80%
“…The influence of colour was less marked with vertical sticky traps than with horizontal water traps, in agreement with the findings of Heathcote (1957). No attempt has been made to relate the effect of sticky trap colour to the wavelength of light emitted since it is known that the adhesive used on sticky traps may considerably affect the spectral reflectance of the original colour (Brach & Trimble, 1985).…”
Section: Discussionsupporting
confidence: 80%
“…Alsynite coated with Tack-Trap had a similar spectral reßectance pattern as untreated clear Alsynite; however, as clear Alsynite visibly yellowed with age, it became Ϸ25% less effective at catching stable ßies (Agee and Patterson 1983). Brach and Trimble (1985) found that the addition of Tangle-Trap to white painted surfaces reduced the reßectance by Ϸ4% in the 400 Ð700-nm range, and by Ͼ50% (from 6.4 to 2.8%) at 360 nm. Both Coroplast and Alsynite had reßectance patterns that overlapped the regions of both maximum spectral sensitivity and phototaxis of stable ßies.…”
Section: Hourly Captures By Coroplast and Alsynite Trapsmentioning
confidence: 93%
“…To test the uniqueness of the optical properties of fibreglass (Zacks & Loew, 1989), a plain Alsynite cylinder trap, and one with Procion Turquoise M-G cloth completely covering the fibreglass on the outside were compared. A sticky sleeve with no cylinder was set nearby on a thin cylindrical wire frame to monitor any innate attractiveness of the adhesive (Brach & Trimble, 1985).…”
Section: Other Biting Fly Trapsmentioning
confidence: 99%